PENGARUH PERKECAMBAHAN TERHADAP KANDUNGAN NUTRISI DAN ASAM SIANIDA BEBERAPA KACANG ARBILA (Phaseolus lunatus L.) LOKAL TIMOR - Gemma G. K. Karangora; Herianus J.D. Lalel; Zainal Abidin; Yuliana Tandi Rubak (JURNAL AGRISA, 2021)
Lima beans (Phaseolus lunatus L.) of local Timor mostly are wildly grown and being used with a long process to reduce their cyanide acid content. Germination has been reported can reduce the anti-nutrition of beans. This research aimed to know the germination effect on nutrition and cyanide acid (HCN) content of several local Timor lima beans, including the black bean, brown bean, white bean, and brownly white bean. The beans were germinated for four days and analyzed for their water content, lipid content, ash content, protein content, carbohydrate content, and HCN content. Results show that after germinating for four days the water content of black bean was 83.43±0.86%, brown bean was 82,10±1,93%, red bean was 81,26±0,66%, and brownly white bean was 82,73±0,69%; lipid content of the black bean was 2,59±0,16%, brown bean was 1,81±0,04%, red bean was 2,17±0,0%, and the brownly white bean was 2,71±0,03%; ash content of the black bean was 0,78±0,03%, brown bean was 0,71±0,01%, red bean was 0,65±0,06%, and the brownly white was 0,80±0,12%; protein content of the black bean was 24,17±0,36%, brown bean was 20,00±0,54%, red bean was 24,49± 0,18%, and the brownly white bean was 23,12±0,71%; the carbohydrate content of black bean was 41,29±2,31%, brown bean was 37.65±0.92%, red bean was 45.15±1.15%, and brownly white bean was 41.77±0.26%. Germination reduced HCN content of beans; after for days of germination, the HCN in back bean, brown bean, red bean, and brownly white bean decreased to be 22.46 ppm, 18.59 ppm, 23.33 ppm, 24.19 ppm, respectively.